UAV Photogrammetry Implementation Based on GNSS CORS UDIP to Enhance Cadastral Surveying and Monitoring Urban Development (Case Study: Ngresep Semarang). (June 2018) - Yuwono, B D; Suprayogi, A; Azeriansyah, R; Nukita, D
Abstract: Unmanned Aerial Vehicle is unique to the field of mechanic which has the ability to fly through the air without a human operator on board, and perform complex and viable option for a number of different tasks, monitoring, coastal environment, cadastre, earthwork analysis. Land Registration is a major issue encountered in developing countries such as Indonesia. Registration of land that had been done in the form of terrestrial measurements expected to be addressed in the next few decades. Monitoring of urban development became a critical problem for urban planning. UAV technology is obtained is used as an alternative to accelerate both processes. The method used in this UAV is photogrammetry to obtain ortho map. The aim of this research is to evaluate the use of UAVs photogrammetry based on GNSS CORS UDIP to enhance cadastral survey and monitoring urban development.